HUBUNGAN ANTARA INTERAKSI SOSIAL DENGAN PERILAKU SEKSUAL PRANIKAH SISWA KELAS X SMK JAKARTA - Sabar Lesmana; Suwandi na (Guidance : Jurnal Bimbingan dan Konseling, 2018)
This research aims to get empiricaldata and information on the relationshipbetween social interaction and premaritalsexual behavior grade SMK X Jakarta 1school year 2016/2017. Research time inDecember to February 2017.The approach in this research isquantitative approach by using thedeskripsif method of penetukorelasional.The population of the research was thewhole grade SMK X Jakarta 1 school year2016/2017 which amounted to 112students. Determination of the number ofsamples using the sample quantityformulation Isaac & Michael i.e. thesample obtained at as many as 87 students.Sampling techniques using simple randomsampling technique that is simple randomtechnique. Data collection research usingquestionnaires/the now closed to bothresearch variables. Before the now givento samples of research conducted testvalidity and reliability test uses productmoment and alpha crombach.The results of this researchobtained values test correlation productmoment obtained rhitungsebesar and rtabelof 0.361 0.962 on a significant level of5%. Thus, r count > r table (0.962 >0.361), means there is a connectionbetween the variable X with variable y.Then rhitung who have obtained thesquared, then r2 = 0.925 results meansocial interaction variables affect variablespremarital sexual behavior of 9.25%significant test result using t-test valuesobtained thitung > ttabel (32.368 > 2.05)which means there is a significantrelationship between social interactionswith premarital sexual behavior of studentsaccepted.The conclusions of this research there weresignificant positive relationships and socialinteractions with premarital sexualbehavior grade SMK X Jakarta 1 schoolyear 2016/2017.